2018
DOI: 10.1016/j.ccell.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The Osteogenic Niche Is a Calcium Reservoir of Bone Micrometastases and Confers Unexpected Therapeutic Vulnerability

Abstract: SUMMARY The fate of disseminated tumor cells is largely determined by microenvironment (ME) niche. The osteogenic niche promotes cancer cell proliferation and bone metastasis progression. We investigated the underlying mechanisms using pre-clinical models and analyses of clinical data. We discovered that the osteogenic niche serves as a calcium (Ca) reservoir for cancer cells through gap junction (GJs). Cancer cells cannot efficiently absorb Ca from ME, but depend on osteogenic cells to increase intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 72 publications
(94 reference statements)
5
110
0
Order By: Relevance
“…Calcium flux, for instance, has been identified as a mechanism of crosstalk between the osteogenic niche and cancer cells, which promotes the progression of bone metastasis. 236 Another example involves patients with postpartum breast cancer, who are at elevated risk for liver metastasis. 237 The identification of the "weaning-induced liver involution," which establishes a metastatic microenvironment, may account, in part, for the poor prognosis of patients with postpartum breast cancer.…”
Section: Extravasationmentioning
confidence: 99%
“…Calcium flux, for instance, has been identified as a mechanism of crosstalk between the osteogenic niche and cancer cells, which promotes the progression of bone metastasis. 236 Another example involves patients with postpartum breast cancer, who are at elevated risk for liver metastasis. 237 The identification of the "weaning-induced liver involution," which establishes a metastatic microenvironment, may account, in part, for the poor prognosis of patients with postpartum breast cancer.…”
Section: Extravasationmentioning
confidence: 99%
“…In particular, the abundant calcium in the bone matrix can attract the calcium-sensing receptor-expressing breast cancer cells to the bone. Furthermore, Wang et al (2018) showed that the increased intracellular calcium concentration in metastatic breast cancer cells induced by connexin 43 can disturb the osteogenic niche and promote survival (Waning et al, 2019). Furthermore, the bone microenvironment promotes breast cancer cells to transit to a migratory phenotype with new malignant capacities.…”
Section: Adhesion and Survivalmentioning
confidence: 99%
“…However, a group of scientists found that intracellular [Ca 2+ ] but not PKC was required for S1P‐induced p42/44 MAPK activation, indicating that PKC exerts a proliferative effect without activating MAPK 32 . Calcium is found mainly in bone, and intracellular [Ca 2+ ] plays an essential role in bone metabolism and metastasis 33‐35 . Therefore, the involvement of the calcium signalling pathway in S1P‐induced osteoblast proliferation significantly improves our understanding of the function of [Ca 2+ ] in bone homeostasis.…”
Section: The Function Of S1p On Osteoclasts and Osteoblastsmentioning
confidence: 99%